Flexural damage behavior of CF/PA6 plain woven laminates with different layers. (1st April 2019) - Zhao, Defang; Ma, Yan; Yang, Yuqiu
Abstract: This study investigated the flexural properties and failure behavior of CF/PA6 plain woven laminates with different layers (i.e., 2, 4, 10 and 16 plies) fabricated by the hot compression technique. Step-by-step interrupted three-point flexural tests and optical observation were performed to study the failure mechanisms of CF/PA6 plain woven laminates with different layers. Incremental cyclic flexural loading tests were carried out to investigate cyclic cumulative damage. The results indicate that the flexural strength of various CF/PA6 plain woven laminates follows the Weibull distribution and that 16-layer laminates show a higher Weibull modulus than the other types of laminates. The flexural initial fracture point (matrix cracking), flexural knee point (intralaminar cracking) have also been identified based on the observation of about 50 specimens for each type. The knee point plays a critical role in determining the flexural properties of composites whereas initial fracture is not a critical factor for the flexural properties. The typical three stages (i.e., initial stage, smooth stage and damage stage) of a fatigue degradation process of various CF/PA6 plain woven laminates during incremental cyclic loading flexural tests were observed. The flexural knee point stress is near the abrupt stiffness degradation limit stress in the present study.